STUDI TENTANG BRAND LOYALITY ( LOYALITAS MEREK ) PRODUK PELEMBAB POND’S ( Studi Pada Warga Perum. Bumi Citra Fajar Sidoarjo Jawa Timur) - Masitha, Raya; Yoestini, Yoestini (Diponegoro Journal of Management, 2013)
Currently,  the competition  among  cosmetic  producers  in Indonesia  is more  glowing,  Many  cosmeticproducers in Indonesia are competing to make the qualified facial moisture product and it admissible to woman kind. The brand product of Pond’s as a market leader of facial moisture in Indonesia is gretting market share decline result from thearrival of competitors those doesn’t inferior. Pond’s was do action in order to all consumers remains loyal to this brand. The research aims to analyze the effect of factor of brand, company, and consumer brand characteristic. Respondent who imvoled within the research is 100 female; method uses non probability sampling, which is accidental sampling. Data collecting is done by distributing questionnaire and data analysis method is performed by multiple linier regression uses SPSS software. The result of regression test demonstrates company,s characteristic variable has a positive and significant  effect  on  brand  loyalty  of  Pond,s  facial  moisture  0,373.  Product  brand,s  characteristic variable  has  a  positive  and  significant  effect  on  brand  loyalty  of  Pond’s  facial  moisture  0,296. Determination  coefficient  value is 0.521 , it means that brand loyalty  is influenced  by characteristic variable  of  brand,  company,  and  costumer-brand  52,1%  ,  where  asa  the  balance  is  48,9%  can  be clarified by other variable those do not examined within this research.